Positive Emotions from Brain Injury: The Emergence of Mirth and Happiness - Mario F. Mendez; Leila Parand (Case Reports in Psychiatry)
Brain injury can result in an increase in positive emotions. We describe a 63-year-old man who presented with a prominent personality change after a gunshot wound to the head. He became “content,” light-hearted, and prone to joking and punning. Prior to his brain injury, he suffered from frequent depression and suicidal ideation, which subsequently resolved. Examination showed a large right calvarial defect and right facial weakness, along with memory impairment and variable executive functions. Further testing was notable for excellent performance on joke comprehension, good facial emotional recognition, adequate Theory of Mind, and elevated happiness. Neuroimaging revealed loss of much of the right frontal and right anterior lobes and left orbitofrontal injury. This patient, and the literature, suggests that frontal predominant injury can facilitate the emergence of mirth along with a sense of increased happiness possibly from disinhibited activation of the subcortical reward/pleasure centers of the ventral striatal limbic area.